On the Face of It: No Differential Sensitivity to Internal Facial Features in the Dog Brain - Szabó, Dóra; Gábor, Anna; Gácsi, Márta; Faragó, Tamás; Kubinyi, Enikő; Miklósi, Ádám; Andics, Attila (Frontiers in Behavioral Neuroscience, 2020)
Dogs are looking at and gaining information from human faces in a variety of contexts. Next to behavioural studies investigating the topic, recent fMRI studies reported face sensitive brain areas in the dogs’ temporal cortex. However, these studies used whole heads as stimuli which contain both internal (eyes, nose, mouth) and external facial features (hair, chin, face-outline). Behavioural studies reported that (1) recognition of human faces by dogs requires visibility of head contour and that (2) dogs are less successful in recognizing their owners from 2D pictures than from real human heads. In contrast, face perception in humans heavily depends on internal features and generalizes to 2D images. Whether putative face sensitive regions in dogs have comparable properties to those of humans has not been tested so far. In two fMRI experiments, we investigated (1) the location of putative face sensitive areas presenting only internal features of a real human face versus a mono-coloured control surface and (2) whether these regions show higher activity toward live human faces and/or static images of those faces compared to scrambled face images, all with the same outline. In Study 1 (n=13) we found strong activity for faces in multiple regions, including the previously described temporo-parietal and occipital regions when the control was a mono-coloured, homogeneous surface. These differences disappeared in Study 2 (n=11) when we compared faces to scrambled faces, controlling for low-level visual cues. Our results do not support the assumption that dogs rely on a specialized brain region for processing internal facial characteristics, which is in line with the behavioural findings regarding dogs’ inability to recognize human faces based on these features.